Immunodetection of phosphorylation sites gives new insights into the mechanisms underlying phospholamban phosphorylation in the intact heart - Mundiña-Weilenmann, Cecilia (1996)
Phosphorylation site-specific antibodies, quantification of 32P incorporation into phospholamban, and simultaneous measurements of mechanical activity were used in Langendorff-perfused rat hearts to provide further insights into the underlying mechanisms of phospholamban phosphorylation. Immunological detection of phospholamban phosphorylation sites showed that the isoproterenol concentration-dependent increase in phospholamban phosphorylation was due to increases in phosphorylation of both Ser16 and Thr17 residues. When isoproterenol concentration was increased at extremely low Ca²⁺ supply to the myocardium, phosphorylation of Thr17 was virtually absent. Under these conditions, 32P incorporation into phospholamban, due to Ser16, decreased by 50%. Changes in Ca²⁺ supply to the myocardium either at constant β-adrenergic stimulation or in the presence of okadaic acid, a phosphatase inhibitor, exclusively modified Thr17 phosphorylation. Changes in phospholamban phosphorylation due to either Ser16 and/or Thr17 were paralleled by changes in myocardial relaxation. The results indicate that cAMP- (Ser16) and Ca²⁺-calmodulin (Thr17)-dependent pathways of phospholamban phosphorylation can occur independently of each other. However, in the absence of β-adrenergic stimulation, phosphorylation of Thr17 could only be detected after simultaneous activation of Ca²⁺-calmodulin-dependent protein kinase and inactivation of phosphatase. It is suggested that under physiological conditions, this requisite is only filled by cAMP-dependent mechanisms.